2009
DOI: 10.1007/978-0-387-72648-9
|View full text |Cite
|
Sign up to set email alerts
|

Geropsychology and Long Term Care

Abstract: except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights.Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 123 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…For example, it may be difficult to find a place to meet that is private. In addition, in such settings it is important to establish clear boundaries about what will and will not be shared with residence staff, both verbally and in written records (Karel, 2009; Knapp & Slattery, 2004; Lichtenberg et al, 1998).…”
Section: Intervention Consultation and Other Service Provisionmentioning
confidence: 99%
“…For example, it may be difficult to find a place to meet that is private. In addition, in such settings it is important to establish clear boundaries about what will and will not be shared with residence staff, both verbally and in written records (Karel, 2009; Knapp & Slattery, 2004; Lichtenberg et al, 1998).…”
Section: Intervention Consultation and Other Service Provisionmentioning
confidence: 99%
“…However, in many homes, especially those in rural areas, it may be a challenge for nursing homes to identify psychologists who are either interested in or prepared to do clinical work and PCC in nursing home settings due to the shortage of geropsychologists in the workforce. Across nursing homes in the United States, psychologists can and do play a central role in culture change through clinical practices that promote PCC (Carney & Norris, 2016;Norris, Molinari, & Ogland-Hand, 2003;Rosowsky, Casciani, & Arnold, 2009), as well as through program development, evaluation, and other research initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some special issues for geropsychology supervision relate to the care settings in which geropsychology practice and training are likely to take place. Many study respondents reported doing training in traditional outpatient mental health settings, and many also reported doing training in nursing home or assisted living (Karel & Moye, 2005; Rosowsky, Casciani, & Arnold, 2009), primary care (Hunter, Goodie, Oordt, & Dobmeyer, 2009; Zweig, Siegel, & Snyder, 2006), and home-based settings (Hicken & Plowhead, 2010), all of which require development of setting-related competencies (Knight et al, 2009). Psychologists providing supervision in these settings need to be familiar with the ethical, clinical, interdisciplinary, and systemic issues particular to these settings and the populations served.…”
Section: Discussionmentioning
confidence: 99%